The Use of Address Terms by Local People in Pedawa Village - Riani, Gusti Ayu Putu Linda (STKIP Agama Hindu Singaraja, 2023)
This study was aimed at finding the types of address terms used in Pedawa village and the social factors which influenced those address terms. Descriptive qualitative was used as the method of this study. The data were collected by conducting observation and interviews through the use of observation sheets and interview guides. There were three local villagers involved as the informants of this study. They were selected by using purposive technique sampling. The collected data were analyzed by using qualitative data analysis through data reduction, data display, and conclusion drawing. The findings show that 1) there are fourteen types of address terms used by local people in Pedawa village covering, kinship terms, teknonym, pet names, title only, first names, occupational terms, religious terms, names, mockery names, pronouns, intimacy names, respect names, endearment terms, and zero address terms, and 2) there six social factors influencing the use of address terms covering family relationship, intimacy, social status, occupational hierarchy, sex, and ethnicity.